Urgensi Literasi Zakat Analisis Kebutuhan Layanan Literasi Zakat Berbasis Web Di Kantor Wilayah Kementerian Agama Provinsi Bengkulu - Septy Veronica (Biro Perencanaan Kementerian Agama, 2022)
The need for zakat information is needed both by the internal ranks of the Regional Office of the Ministry of Religion itself and the community. Several complaints related to access to zakat information so far submitted by information needers are time efficiency in obtaining zakat literacy. This study uses a descriptive method with a qualitative approach. That is research that seeks to describe and interpret phenomena that are happening in the field This, of course, requires an action to change so that in the future zakat information services can be obtained more quickly by those who need it. Based on APKL analysis, it is known that the priority problem for intervention or change is that zakat literacy services are still not optimal. And based on USG analysis, it is known that WEB-based zakat literacy is needed at the Regional Office of the Ministry of Religion of Bengkulu Province. Keywords: Zakat Literature; Service; Anayisis.